FAKTOR PENDUKUNG TINGKAT KELULUSAN WARGA BELAJAR PADA PROGRAM PENDIDIKAN KESETARAAN PAKET C DI PKBM SINGGALANG SAIYO KABUPATEN TANAH DATAR SUMATERA BARAT - Nuratika, Nuratika; Wilson, Wilson; Irja, Desti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this research is to determine internal factors as a supportive factor for graduation and to know external factors as supporting factors for graduation. This research uses a descriptive method with a qualitative approach. The informants of this study consisted of 4 informants, namely key informant 1, key informant 2, control informant and observer informant. Techniques for data collection are observation, interview, documentation and data validity. The process of data analysis takes place simultaneously with the process of data collection, namely data collection, data reduction, data presentation and conclusions or verification. The results of this study indicate that internal factors are quite high and external factors are high.Key Words: Supporting Factors, Level C. Package Pass